Residential segregation and location patterns of the foreign-born population based on spatial indicators. The case of the metropolitan area of Las Palmas de Gran Canaria (Spain) (Ciudades, 2025)
In the last two decades, the immigrant population of foreign origin has increased in Spanish cities. The metropolitan area of Las Palmas de Gran Canaria (Large Urban Area) is a clear example in an insular and ultraperipheral context. This article analyses the levels of segregation and the location patterns of the foreign-origin population in this area over time in order to establish a location model based on the spatial analysis of bivariate correlations with income. A statistically significant model is established and the role played by this population in relation to the real estate network is indicated.
Keywords: residential segregation; foreign-bom; residential location model; income; bivariate Moran index